Hardware security threats and countermeasures: a study of obfuscation, camouflaging and PUFs. (29th January 2020) - Maharmeh, Hamza Al; Alhawari, Mohammad; Hung, Chung-Chih; Ismail, Mohammed
Hardware security threats have gained a tremendous attention where extensive research efforts have been expended toward developing effective countermeasures. These threats can be categorised into five main attacks which are: reverse engineering, side-channel analysis, intellectual property (IP) cores piracy/IC overbuilding, counterfeiting, and hardware Trojans. This paper investigates the most efficient state-of-the-art techniques that are used to thwart main hardware attacks. Reported work in the literature proposed various countermeasures, where obfuscation, camouflaging, and physically unclonable functions (PUFs) are considered the most powerful and effective methods. In obfuscation technique, the chip will be locked and it will not function properly unless the correct secret key is supplied. This paper addresses also camouflaging countermeasure which is a layout-based technique that is used to protect IP cores. Additionally, this paper provides a detailed study on silicon PUFs, where they can be classified into weak and strong PUFs. In this paper, various PUF architectures will be discussed along with the design constraints.